Survival of cheese-ripening microorganisms in a dynamic simulator of the gastrointestinal tract. (February 2016) - Adouard, Nadège; Magne, Laurent; Cattenoz, Thomas; Guillemin, Hervé; Foligné, Benoît; Picque, Daniel; Bonnarme, Pascal
Abstract: A mixture of nine microorganisms (six bacteria and three yeasts) from the microflora of surface-ripened cheeses were subjected to in vitro digestive stress in a three-compartment "dynamic gastrointestinal digester" (DIDGI). We studied the microorganisms (i) grown separately in culture medium only (ii) grown separately in culture medium and then mixed, (iii) grown separately in culture medium and then included in a rennet gel and (iv) grown together in smear-ripened cheese. The yeasts Geotrichum candidum, Kluyveromyces lactis and Debaryomyces hansenii, were strongly resistant to the whole DIDGI process (with a drop in viable cell counts of less than <1 log CFU mL −1 ) and there were no significant differences between lab cultures and cheese-grown cultures. Ripening bacteria such as Hafnia alvei survived gastric stress less well when grown in cheese (with no viable cells after 90 min of exposure of the cheese matrix, compared with 6 CFU mL −1 in lab cultures). The ability of Corynebacterium casei and Staphylococcus equorum to withstand digestive stress was similar for cheese and pure culture conditions. When grow in a cheese matrix, Brevibacterium aurantiacum and Arthrobacter arilaitensis were clearly more sensitive to the overall digestive process than when grown in pure cultures. Lactococcus lactis displayed poorer survival in gastric and duodenal compartments when it had been grown in cheese. In vivo experiments in BALB/c mice agreed with the DIDGI experiments and confirmed the latter's reliability. Highlights: We designed a dynamic, three-stage in vitro simulator of the gastrointestinal tract. The simulator was used to test how cheese-ripening microflora resist digestive stress when grown in a real cheese matrix. Growth in real cheese had an impact on the microorganisms' ability to withstand further digestive stress. The results of in vivo studies in the mouse confirmed our in vitro observations. The cheese matrix's buffering capacity proved to be of importance in the choice of in vitro digestive parameters.